DARIAKIW! proszę ktoś umie na teraz, ktoś dobry z matmy ?

a) 2x - 3y + 4z² - 7x + 12y - 3z² = -5x + 9y + z² = -5 · 2 + 9·(-2) + (1/2)² =
-10 - 18 + 1/4 = -28 + 1/4 = -27 3/4
b)0,6y²z -0,2x²y + 1,4zy² -0,8yx² -2 = y( 0,6yz - 0,2x² + 1,4yz -0,8x²) -2
y(2yz - x²) - 2 = -2(2 · (-2) ·1/2 - 2²) -2 = -2 ( -2 -4) - 2 = 12 - 2 = 10
c) 2yx²z - 3xyz³ -4x²yz -6z³xy -yxz² = xyz (2x -3z² -4x -6z² -z) =
xyz (-2x -9z² -z) = 2·(-2)·1/2 ( -2·2 -9· 1/2² -1/2) = -2( -4 -9/4 - 2/4) =
-2(-4 - 11/4) = 8 + 22/4 = 8 + 5 1/2 = 13 1/2
z góry sorki jak gdzieś się pomyliłam